Kebijakan Produk Global Menghadapi Tantangan di Era Ekonomi Digital dan Globalisasi - Ardhinur Ardhinur; M. Difach Hazairin Nst; Syakira Rifdahayani Yoes; Suhairi Suhairi (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
Global product policy facing challenges in the digitalization era is a new challenge for manufacturers who market their products internationally and this is a challenge that must be handled by means of marketing research, digital marketing through social media and also making their own applications, and also using Global store as a public puller for these products. The research used a descriptive qualitative research methodology with literature study techniques which sourced from readings such as journals, news sources, books and also facts on the ground which were clearly explained and led to a result which was then concluded as a research result. The results of this study conclude that only companies that are going to market their products or so far after marketing their products to international shores must follow the development of basic marketing digitalization as well as manufacturers who have never marketed their products abroad and also use international or global figures as brands. and attractiveness for consumers who will buy the product.